2000
DOI: 10.1161/01.hyp.35.5.1055
|View full text |Cite
|
Sign up to set email alerts
|

Vascular NADH/NADPH Oxidase Is Involved in Enhanced Superoxide Production in Spontaneously Hypertensive Rats

Abstract: Abstract-This study was designed to test the hypothesis that stimulation of nicotinamide adenine dinucleotide/ nicotinamide adenine dinucleotide phosphate (NADH/NADPH) oxidase is involved in increased vascular superoxide anion (⅐O 2 Ϫ ) production in spontaneously hypertensive rats (SHR). The study was performed in 16-week-old and 30-week-old normotensive Wistar-Kyoto rats (WKY 16 and WKY 30 , respectively) and in 16-week-old and 30-week-old SHR (SHR 16 and SHR 30 , respectively). In addition, 16-week-old SHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
246
0
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(274 citation statements)
references
References 50 publications
19
246
0
9
Order By: Relevance
“…Alternatively, the increased NADPH oxidase activity may come from the upregulated expression of NADPH oxidase. In aorta of DOCA-salt hypertensive rats, p22 phox mRNA is increased, accompanied with an increased NADPH oxidase activity (49). In vivo ANG II treatment (7 days) in rats upregulates the expression of NADPH oxidase subunits and significantly increases NADPH oxidase activity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the increased NADPH oxidase activity may come from the upregulated expression of NADPH oxidase. In aorta of DOCA-salt hypertensive rats, p22 phox mRNA is increased, accompanied with an increased NADPH oxidase activity (49). In vivo ANG II treatment (7 days) in rats upregulates the expression of NADPH oxidase subunits and significantly increases NADPH oxidase activity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Zalba et al 27 demonstrated increased production of superoxide anion in SHRs. Conversely, animal studies showed that the attenuation of cellular oxidative stress by overexpression of superoxide dismutase (SOD) or treatment with antioxidants attenuated these blood pressure elevations.…”
Section: Interaction Of Oxidative Stress and Inflammation In The Devementioning
confidence: 97%
“…59,60,68 Ang II-induced NADPH oxidase activation is one of the major sources of ROS in atherosclerosis. 18,19,67,68 Zalba et al 68 showed that endothelial dysfunction is due to an excess of ROS rather than a decrease in NO production in the aorta of spontaneously hypertensive rats and is associated with both upregulation of p22 phox mRNA expression and increased activity of NADPH oxidase. Upregulation of p22 phox mRNA expression is a key component of Ang II-induced NADPH oxidase activation, and increased expression levels of other components also have an important role in this oxidase under pathological conditions.…”
Section: Oxidative Stressmentioning
confidence: 99%